Therapeutic roles of natural and engineered mesenchymal stem cells and extracellular vesicles in atopic dermatitis - Ren, Tingting; He, Kang; Xu, Donghua; Kong, Yuxiang; Jiang, Shuyue; Chu, Jinjin; Sun, Yi; Zang, Jie; Wang, Zhenhua (Regenerative therapy, 2025)
Atopic dermatitis (AD) is a chronic and inflammatory disease characterized by skin barrier destruction, sustained inflammation, and immune imbalance. Increasing evidence has suggested mesenchymal stem cells (MSCs) exhibit great potentials in treating AD due to the strong anti-inflammatory, immunomodulatory, and regenerative repair properties. As a cell-free nanocarrier, MSC-derived extracellular vesicles (MSC-EVs) play critical roles in mediating intercellular communications. Recent advance has suggested some bioengineering strategies have greatly improved the therapeutic potentials of MSCs and MSC-EVs in AD treatment, such as genetic reprogramming, biomimetic scaffold integration, and precision surface functionalization. In this comprehensive review, we systematically evaluate the current landscape of both natural and engineered MSCs and MSC-EVs to provide updated insights into the exploration of therapeutic strategies for AD.